MULTICULTURAL EDUCATION FOR ISLAMIC ELEMENTARY SCHOOL STUDENTS - nisfi anisah (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2017)
Pluralism is as one of the uniqueness of each individual or group. Attitudes and behavior of mutual tolerance and mutual respect should be developed early on learners. School as an educational institution became one of the multicultural education implementation agencies. The learning process in schools geared to appreciate the differences that exist in each learner as well as other school communities. The implementation of multicultural education in Islamic elementary school in Indonesia has been carried out by a change curriculum policy and the implementation of values multicultural loaded on subjects, for example on the subjects of citizenship, religious education. Islamic Elementary Muhammadiyah Sendangmulyo is a school which is receive of implementing multicultural education with undiscriminating acceptance of learners in terms of a difference religion. One of the non-Muslims students in this school won Islamic competion Islamic religion in Kulonprogo. However, in Islamic elementary Muhammadiyah Sendangmulyo there is no religious lesson other than Islamic religious lesson.